FAKTOR-FAKTOR YANG MEMPENGARUHI KEMISKINAN RELATIF DI KOTA BANDA ACEH. - Sandra Andria, Abubakar Hamzah, Muhammad Nasir. (Jurnal Ilmu Ekonomi : Program Pascasarjana Unsyiah, 2014)
Abstract: This study aims to determine the factors affecting poverty in Banda Aceh City. The sample was as much as 69 households in 4 (four) villages in 4 (four) districts in Banda Aceh City. The data in this study is primary data and secondary data. The model analysis is a logitics regression where the independent variables are qualitative while the dependent variable is the household characteristics, community factors, and characteristics of the region. The research showed that the factor of households and individuals characteristics is the most important factor affecting poverty in Banda Aceh City. These factors include the head of household education, household size, number of family members working, the head of the family work status, region of origin family background, home ownership status and the ability of family for entrepreneurship. Furthermore, the factors that significantly influence community poverty is the condition of the main road in the village of residence. While the existence of financial institutions that facilitate people's access to capital, the presence of small-scale industries like cottage industries for the community and range the village to city center has no significant effect on poverty. Instead factor characteristics of the region (the availability of acreage / land sufficient to carry out production activities and within the area / village where the coast / beaches) is not a determinant of poverty. This means that poverty suffered a household is not significantly related to regional characteristics factors. For that government efforts to reduce the number of poor households should be directed toward improving the community factor, especially roads and other rural infrastructure, and improve individual and household characteristics primarily related to level of education, level of education, the ability to obtain employment, and the ability of households for enterpreneurship. Keywords: Household and individual characteristics, community factors, regional characteristics factor, poverty and logistic models.